Nintedanib Alleviates Experimental Colitis by Inhibiting CEBPB/PCK1 and CEBPB/EFNA1 Pathways - Li, Hailong; Li, Jinhe; Xiao, Ting; Hu, Yayue; Yang, Ying; Gu, Xiaoting; Jin, Ge; Cao, Hailong; Zhou, Honggang; Yang, Cheng (Frontiers in Pharmacology, 2022)
Super-enhancer, a cluster of enhancers with strong transcriptional activity, has become one of the most interesting topics in recent years. This study aimed to investigate pathogenic super-enhancer-driven genes in IBD and screen therapeutic drugs based on this. In this study, through the analysis of differentially expressed genes in colitis patients from the GEO database and the analysis of super-enhancer associated database, we found that the super-enhancer pathogenic genes PCK1 and EFNA1 were simultaneously regulated by transcription factor CEBPB through two super-enhancers (sc-CHR20-57528535 and sc-CHR1-155093980). Silencing CEBPB could significantly inhibit the expression of PCK1 and EFNA1, and enhance the expression of epithelial barrier proteins claudin-1, occludin and ZO-1. In LPS-induced Caco-2 cells, drugs commonly used in clinical colitis including tofacitinib, oxalazine, mesalazine and sulfasalazine all inhibited mRNA levels of CEBPB, PCK1 and EFNA1. In the drug screen, we found that nintedanib significantly inhibited the mRNA and protein levels of CEBPB, PCK1 and EFNA1. In vivo experiments, nintedanib significantly alleviated DSS induced colitis in mice by inhibiting CEBPB/PCK1 and CEBPB/EFNA1 signaling pathways. At the genus level, nintedanib improved the composition of the gut microbiota in mice with DSS induced experimental colitis. In conclusion, we found that PCK1 and EFNA1 are high-expressed in colitis and they are regulated by CEBPB through two super-enhancers, and we further demonstrate their role in vivo and in vitro. Nintedanib may be a potential treatment for IBD. Super-enhancers may be a new way to explore the pathogenesis of colitis.